1997
DOI: 10.1007/s004200050215
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological investigation of central, peripheral and autonomic nerve function in workers with long-term low-level exposure to carbon disulphide in the viscose industry

Abstract: Isolated decrease of MNCV in binary evaluation is, with regard to the known mechanism of CS2-neurotoxicity and the lack of a dose-response relationship, obviously not due to toxic effects. We interpret our results as showing that an adverse effect of carbon disulphide at the exposure ranges found was not detectable in the exposed group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Age is often used as a covariate such as in the ARIC, FHS, and Whitehall studies. In those studies that have specifically investigated the relationship between age and cardiac function, consistent evidence supports this relationship [53]. For example Antelmi et al [52] investigated the association between age and vagal tone in 292 men and 361 women aged from 14 to 82 years.…”
Section: Non-modifiable Risk Factors: Age and Family Historymentioning
confidence: 92%
“…Age is often used as a covariate such as in the ARIC, FHS, and Whitehall studies. In those studies that have specifically investigated the relationship between age and cardiac function, consistent evidence supports this relationship [53]. For example Antelmi et al [52] investigated the association between age and vagal tone in 292 men and 361 women aged from 14 to 82 years.…”
Section: Non-modifiable Risk Factors: Age and Family Historymentioning
confidence: 92%
“…These effects have been observed in workers exposed to CS2 at 1.0 ppm or above. In contrast, other studies on viscose rayon workers exposed to equal concentrations of CS2 have shown little indication of an effect on NCV 11,14 ) . Furthermore, NCV in the present CS2 exposed group was lower than that removed from the CS2 exposure group on a cross-sectional observation 9) .…”
Section: Introductionmentioning
confidence: 89%
“…Toxicity is most often manifested as slower nerve conduction velocity (NCV) in the peripheral nerves 1,7 ) and impaired performance in psychomotor testing 8) . Peripheral nervous system effects have been reported in many cross-sectional studies on workers exposed to CS2 in the viscose rayon industry 1,7,[9][10][11][12][13]14) . The most common observations are characterized by slower motor (MCV) and sensory nerve conduction velocity (SCV) 1,7,9,15) .…”
Section: Introductionmentioning
confidence: 99%
“… Hazardous substances Neurotoxic substances can lead to a reduction in the HRV: e.g. carbon disulphide [ 169 , 170 ], however, not in the case of long-term low-dose exposure [ 171 ]; acute diesel and biodiesel inhalation [ 172 ]; chronic lead [ 173 , 174 ], acute cadmium [ 175 ] or long-term mercury exposures [ 176 ] and neurotoxic styrene exposure [ 177 , 178 ]. The data regarding the effects of chronic solvent exposure is not conclusive, both - a fall in the HRV and no differences - have been described [ 179 181 ].…”
Section: Determination Of the Nn Intervals For The Calculation Of Hr ...mentioning
confidence: 99%